Damping and noise-reducing polyphenylene sulfide composite material and preparation method thereof
By adding shape memory polymer and high compressive strength hollow glass microbeads to the polyphenylene sulfide material, combined with a specific extrusion process, the vibration noise problem of polyphenylene sulfide material is solved, and effective damping and noise reduction effect is achieved , avoiding the risk of microbeads being damaged during processing.
Patent Information
- Application Number
- CN202411472336.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-10
AI Technical Summary
Polyphenylene sulfide materials are used due to their rigid properties to cause vibration noise problems. The prior art reduces noise by increasing hollow glass microbeads, but is prone to shear damage during screw extrusion processing, making it difficult to achieve the expected noise reduction effect.
Add shape memory polymer and appropriate amount of hollow glass microbeads to the polyphenylene sulfide composite material, and use the shape recovery function of the shape memory polymer to absorb vibration energy, combined with high pressure resistance The strength of hollow glass beads is kneaded under low viscosity conditions to ensure its integrity to achieve damping and noise reduction.
Effectively absorb and dissipate vibration energy, significantly reduce noise and vibration, improve the toughness and impact resistance of composite materials, and avoid damage to hollow glass microbeads during processing, improving noise reduction effect.
Smart Images

Figure CN119286251A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of special engineering plastics, and in particular to a damping and noise-reducing polyphenylene sulfide composite material and a preparation method thereof. Background Art
[0002] With the rapid development of new energy vehicles and aerospace industries, the demand for lightweight materials has increased dramatically. Plastic composite materials have become the mainstream technology to replace metal materials due to their light weight and easy processing and molding.
[0003] Polyphenylene sulfide has excellent high temperature resistance, wear resistance, chemical corrosion resistance and flame retardancy up to UL94 V-0. It can be used for a long time at a high temperature of 220°C and can withstand an instantaneous temperature of up to 275°C. At the same time, polyphenylene sulfide has the same rigidity as metal, and its mechanical properties are among the best in engineering plastics.
[0004] By tempering polyphenylene sulfide with glass fiber, the weight can be reduced by up to 60% compared with metal, and the fatigue resistance can be increased by more than 2 times. It can replace metal as a special engineering material and be applied in many industries. Currently, polyphenylene sulfide is used as a metal replacement material in many industries such as electronics, automobiles, aviation, new energy, and transportation.
[0005] Polyphenylene sulfide can replace metal in large products, such as automobile cylinder head covers, which has a significant weight reduction effect. Traditional automobile engine cylinder head covers are mainly made of gray cast iron, alloy cast iron or aluminum alloy, which is not only expensive but also heavy. Using polyphenylene sulfide to replace traditional metal cylinder head covers has become a development trend.
[0006] When the engine cylinder head cover made of polyphenylene sulfide is applied to the engine, the vibration generated by the operation of the engine will be transmitted to the engine cover, causing vibration noise of the engine cover. In practical use, users hope that this noise can be reduced to improve the driving comfort of the vehicle, thus raising the demand for noise reduction of polyphenylene sulfide.
[0007] Polyphenylene sulfide has the characteristic of rigidity, so it is easy to generate noise when vibrating. In order to reduce the vibration noise of polyphenylene sulfide, a certain noise reduction improvement can be obtained by dispersing hollow glass microspheres in polyphenylene sulfide. Chinese invention patent publication number CN103173014A discloses a lightweight noise reduction polyphenylene sulfide material, which is made of the following components in parts by weight: 60-70 parts of polyphenylene sulfide, 10-20 parts of glass microspheres, 10-30 parts of glass fiber, 0.2-0.5 parts of lubricant, 0.5-0.8 parts of antioxidant, and 0.5-0.9 parts of coupling agent. Polyphenylene sulfide is reinforced with glass fiber and filled with glass microspheres. The hollow structure of the glass microspheres achieves the effect of reducing the overall density of polyphenylene sulfide, while improving the mechanical properties of the material while maintaining the low density of the material. At the same time, the special structure of the hollow particles of the glass microspheres also gives the material a certain noise reduction function.
[0008] However, in order to achieve good noise reduction, it is usually necessary to add more hollow glass beads, but more glass beads are easily sheared and broken during the processing of the screw extruder, making it difficult to achieve the desired noise reduction purpose. Summary of the invention
[0009] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a damping and noise-reducing polyphenylene sulfide composite material and a preparation method thereof.
[0010] The objective of the present invention is achieved through the following technical solutions:
[0011] A damping and noise reduction polyphenylene sulfide composite material and a preparation method thereof, comprising the following raw material components in parts by weight: 40-55 parts of polyphenylene sulfide, 35-45 parts of glass fiber, 3-5 parts of shape memory polymer, 3-5 parts of hollow glass microbeads, 0.3-0.5 parts of lubricant, 0.2-0.5 parts of coupling agent and 0-2 parts of masterbatch.
[0012] The shape memory polymer is called a shape memory polymer, which refers to a polymer material that can restore its original shape after the initial condition of a product is changed and fixed under certain conditions, and then stimulated by external conditions (such as heat, electricity, light, chemical induction, etc.).
[0013] The addition of the shape memory polymer gives the composite material a shape memory function, which may restore the original shape or change the shape under specific conditions (such as temperature and pressure changes), thereby increasing the flexibility and functionality of the material.
[0014] In the above technical solution of the present invention, the shape memory polymer has a unique shape memory function and can restore the original shape under certain conditions. This property helps to absorb and dissipate vibration energy, thereby achieving the effect of damping and noise reduction. The addition of shape memory polymer can also improve the toughness and impact resistance of the composite material to a certain extent.
[0015] In some preferred embodiments, the shape memory polymer is preferably polyurethane and / or styrene-butadiene-styrene triblock copolymer.
[0016] Among them, polyurethane has excellent shape memory function and can return to its original shape under certain conditions (such as heating). This property enables polyurethane to effectively absorb and dissipate vibration energy in composite materials, providing additional functionality and flexibility, thereby achieving the effect of damping and noise reduction. Styrene-butadiene-styrene triblock copolymer, as a thermoplastic elastomer, has excellent damping properties. It can effectively absorb and dissipate vibration energy, thereby significantly reducing noise and vibration.
[0017] In some preferred embodiments, the shape memory polymer is selected from a cross-linked polymer of polyurethane and epoxy resin and / or a styrene-butadiene-styrene triblock copolymer blended with a linear low density polyethylene (LLDPE) by benzoyl peroxide.
[0018] Among them, cross-linked polymers of polyurethane and epoxy resin have significant advantages in mechanical properties, shape memory properties and thermal stability, and are suitable for fields that require high strength, high durability and shape memory functions. Styrene-butadiene-styrene triblock copolymers blended with linear low-density polyethylene (LLDPE) can be treated with benzoyl peroxide to improve compatibility, adjust mechanical properties and optimize processing properties. Although it does not directly impart shape memory properties, it provides the possibility for the development of new shape memory materials.
[0019] In some preferred embodiments, the hollow glass microspheres have a particle size of 20 μm and a compressive strength of ≥110 MPa.
[0020] Among them, the particle size of 20μm enables the hollow glass microspheres to be more evenly dispersed in the polyphenylene sulfide matrix, reducing agglomeration, thereby improving the overall performance of the composite material; the appropriate particle size helps to form more air gaps, which play a hindering role in the propagation of sound waves, thereby improving the damping and noise reduction effect of the composite material. High compressive strength ensures that the hollow glass microspheres are not easy to break during the processing and use of the composite material, maintaining its complete hollow structure, thereby continuing to play a role in sound insulation and noise reduction. High compressive strength also means that the hollow glass microspheres themselves have a certain load-bearing capacity, which helps to improve the overall mechanical properties of the composite material, such as compressive strength and impact resistance.
[0021] In some preferred embodiments, the glass fiber is selected from alkali-free continuous glass fiber.
[0022] Among them, the tensile strength and modulus of alkali-free continuous glass fiber are relatively high, which enables it to significantly improve the mechanical strength and stiffness of composite materials when used as a reinforcing material, and improve wear resistance and corrosion resistance.
[0023] In some preferred embodiments, the lubricant is selected from one or more of silicone powder, silicone masterbatch, and rice bran wax.
[0024] Among them, lubricants can reduce friction and wear of materials during the melt extrusion process, reduce energy consumption, and improve extrusion efficiency and product quality; lubricants can improve the fluidity of composite materials, making them easier to process and shape, and reduce defects and scrap rates; natural lubricants such as rice bran wax also have the advantages of being environmentally friendly and non-toxic, and meet the requirements of modern green manufacturing.
[0025] In some preferred embodiments, the coupling agent is a silane coupling agent.
[0026] Among them, silane coupling agents form bridges between inorganic fillers (such as hollow glass microspheres, glass fibers) and organic matrices (such as polyphenylene sulfide) through chemical bonding, enhancing the interfacial bonding between them. This helps to improve the overall performance and stability of the composite material; silane coupling agents can also improve the hydrolysis resistance and chemical resistance of the composite material, allowing it to maintain stable performance in humid or corrosive environments. This is especially important for outdoor applications or scenarios that require long-term use.
[0027] In some preferred embodiments, S1: 40-55 parts of the polyphenylene sulfide, 3-5 parts of the shape memory polymer, 0.3-0.5 parts of the lubricant, and 0-2 parts of the masterbatch are mixed at a high speed and dispersed uniformly to obtain a mixture;
[0028] S2: adding the mixed material into a co-rotating twin-screw extruder for melt extrusion granulation, adding 35-45 parts of alkali-free continuous glass fiber, 3-5 parts of hollow glass microbeads and 0.2-0.5 parts of coupling agent during the melt extrusion granulation process, screening and drying after granulation to obtain the damping and noise reduction polyphenylene sulfide composite material.
[0029] Among them, the high-speed mixing process ensures the uniform dispersion of each component in the polyphenylene sulfide matrix, avoiding the performance difference caused by uneven distribution of components. The addition of shape memory polymer gives the composite material shape memory function, increasing its intelligence and versatility. The use of lubricant improves the processing performance of the mixture. By adding an appropriate amount of masterbatch, the color of the composite material can be flexibly adjusted to meet different design requirements. The addition of alkali-free continuous glass fiber significantly improves the mechanical strength and stiffness of the composite material, enabling it to withstand greater loads and stresses. Hollow glass microspheres, as lightweight fillers, effectively reduce the density of the composite material, making it lighter, easier to process and transport. The use of coupling agent enhances the interfacial bonding between glass fiber and polyphenylene sulfide matrix, reduces the occurrence of interface defects and stress concentration, and improves the overall performance and stability of the composite material. The co-rotating twin-screw extruder with a suitable aspect ratio is selected, and the temperature of each zone is precisely controlled to ensure uniform melting and good dispersion of the material during the extrusion process, thereby improving processing efficiency and product quality.
[0030] In some preferred embodiments: wherein the length-to-diameter ratio of the screw of the co-rotating twin-screw extruder is 35:1, and it includes ten extrusion temperature control zones in sequence, and the extrusion temperature control of each zone is: zone 1 220-260°C; zone 2 280-300°C; zone 3 310-320°C; zone 4 280-290°C; zone 5 220-260°C; zone 6 240-260°C; zone 7 290-300°C; zone 8 290-300°C; zone 9 290-300°C and zone 10 300-320°C.
[0031] Among them, the temperature of zone 1 is relatively low, which is mainly used to preheat the material to soften it gradually and prepare for subsequent high-temperature melting; it avoids excessive thermal stress caused by the material directly entering the high-temperature area, which helps to protect the material structure and performance. In zone 2, the material begins to melt initially in this area to form a melt, which provides a basis for subsequent mixing and extrusion; the appropriate high temperature helps the mutual penetration and mixing of materials and improves the mixing efficiency. In zone 3, the material is further melted in this area to ensure the formation of a uniform melt; the high temperature helps the material to be fully plasticized and improve the plasticization quality of the composite material. The temperature of zone 4 is slightly lower than that of zone 3, which helps to adjust the temperature distribution of the melt and avoid overheating; it provides a stable melt temperature for the subsequent extrusion process to ensure the extrusion quality. Zone 5 preheats the melt that may drop in temperature due to flow again to keep its temperature stable; by lowering the temperature setting, unnecessary energy consumption is reduced. In zone 6, these areas maintain a high temperature to ensure that the material continues to melt and is fully mixed; stable temperature control helps to maintain the stability of the extrusion process and improve product quality; high temperature helps the material to be further plasticized and improve the overall performance of the composite material. Zone 10 is the final melting zone, which ensures that the material is completely melted and extruded smoothly; by adjusting the temperature of this zone, the temperature of the extrudate can be fine-tuned to meet the needs of subsequent processing or use.
[0032] In some preferred embodiments: the alkali-free continuous glass fiber is added from the feeding port on the fifth zone side; the hollow glass microspheres are added from the feeding port on the seventh zone side; and the coupling agent is added from the feeding port on the eighth zone side.
[0033] Among them, the temperature of the fifth zone is set at 220-260℃, which can not only keep the glass fiber rigid, but also help it to contact and wet the polyphenylene sulfide matrix. At this time, the addition of glass fiber will not soften rapidly due to excessive temperature, thus maintaining its good reinforcement effect. On the basis that the molten materials have been initially mixed and plasticized, the addition of glass fiber can further promote the mixing of materials and improve the uniformity of the composite material. The temperature of the seventh zone is set at 290-300℃. At this time, the addition of hollow glass microspheres can avoid damage due to direct exposure to excessively high temperatures, and maintain its complete spherical structure and excellent physical properties. On the basis that the materials have been fully melted and mixed, the addition of hollow glass microspheres can be more evenly filled in the polyphenylene sulfide matrix, reduce voids and defects, and improve the density and mechanical properties of the composite material. The addition of coupling agent in the eighth zone mainly improves the interfacial bonding between inorganic fillers (such as glass fibers) and organic matrices (such as polyphenylene sulfide). At this time, the materials have been fully melted and mixed evenly, and the coupling agent can act more effectively between the glass fiber and the polyphenylene sulfide matrix to form a strong interface layer and improve the overall performance of the composite material.
[0034] The beneficial effects of the present invention are:
[0035] 1) The present invention uses a shape memory polymer in a glass fiber reinforced polyphenylene sulfide system. When subjected to external vibration energy, the molecular chain segments change their conformation through internal rotation in the main chain, and at the same time, they move, slip, and disentangle to generate internal friction, thereby instantly converting the external vibration energy into heat energy dissipation, thereby achieving damping and noise reduction.
[0036] 2) During extrusion granulation, the present invention adds hollow glass microspheres after the glass fibers are sheared, and finally adds a coupling agent, so that the hollow glass microspheres are mixed under low viscosity conditions, thereby ensuring that the hollow glass microspheres are not easily sheared and damaged during processing by a screw extruder, and further synergistically improving the damping and noise reduction effect.
[0037] 3) The present invention adds shape memory polymer through side feeding, and partially or completely recovers to the previous state due to elasticity, thereby maintaining the stability of the product structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is the cylinder head cover vibration measurement point and the near-field 20cm noise measurement point diagram; DETAILED DESCRIPTION
[0039] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0040] Example 1
[0041] The damping and noise reduction polyphenylene sulfide composite material was prepared by the following steps:
[0042] (1) According to the weight ratio of the formula, 40 parts of polyphenylene sulfide, styrene-butadiene-styrene triblock polymer (SBS) and linear low-density polyethylene (LLDPE) are blended and cross-linked by benzoyl peroxide to obtain an interpenetrating network polymer of 5 parts, 0.5 parts of rice bran wax, and 1.0 parts of black masterbatch are added into a high-speed mixer and dispersed evenly; the mixture is transported to a storage bin for standby use;
[0043] 0.5 parts of rice bran wax and 1.0 parts of black masterbatch are added to a high-speed mixer and dispersed evenly; the mixed material is transported to a storage bin for standby use; (2) the mixed material is weighed by a loss-in-weight scale and added to a co-rotating twin-screw extruder for melt extrusion and granulation, wherein the co-rotating twin-screw extruder uses a screw length-to-diameter ratio of 35:1; the extrusion temperature of each zone is: 220°C for zone 1; 280°C for zone 2; 310°C for zone 3; 290°C for zone 4; 260°C for zone 5; 240°C for zone 6; 290°C for zone 7; 300°C for zone 8; 300°C for zone 9; and 300°C for zone 10. The temperature of the zone is 320℃; alkali-free continuous glass fiber is added to the side feeding port of the fifth zone, and the amount of glass fiber added is ensured to be 45 parts by controlling the screw speed and the number of glass fiber strands added; 5 parts of hollow glass microbeads (brand iM16K) are added to the side feeding port of the seventh zone through a loss-in-weight scale; 0.3 parts of silane coupling agent (brand KH-560) are pumped into the side feeding port of the eighth zone through a metering pump; a damping and noise-reducing polyphenylene sulfide composite material is obtained by screw shearing dispersion, melt extrusion, water-cooled strand cutting, screening, drying and packaging.
[0044] Embodiment 2:
[0045] (1) Add 40 parts of polyphenylene sulfide, 5 parts of interpenetrating network polymer cross-linked by polyurethane and epoxy resin, 0.5 parts of silicone powder, and 1.0 parts of black masterbatch into a high-speed mixer and disperse them evenly; transport the mixture to a storage bin for standby use;
[0046] (2) The mixed material is weighed by a loss-in-weight scale and added to a co-rotating twin-screw extruder for melt extrusion and granulation, wherein the co-rotating twin-screw extruder uses a screw length-diameter ratio of 35:1; the extrusion temperature of each zone is controlled as follows: zone 1 220°C; zone 2 280°C; zone 3 310°C; zone 4 290°C; zone 5 260°C; zone 6 240°C; zone 7 290°C; zone 8 300°C; zone 9 300°C; zone 10 320°C; alkali-free continuous glass fiber is added to the side feed port of zone 5 , by controlling the screw speed and the number of glass fiber added, ensuring that the amount of glass fiber added is 45 parts; adding 4 parts of hollow glass microbeads (brand iM16K) through a loss-in-weight scale at the side feeding port of zone seven; pumping 0.3 parts of silane coupling agent (brand KH-560) into the side feeding port of zone eight through a metering pump; through screw shearing dispersion, melt extrusion, water-cooled strand pelletizing, screening, drying and packaging, a damping and noise reduction polyphenylene sulfide composite material is obtained.
[0047] Embodiment 3:
[0048] (1) According to the weight ratio of the formula, 40 parts of polyphenylene sulfide, 5 parts of interpenetrating network polymer obtained by blending SBS and LLDPE and cross-linking initiated by benzoyl peroxide, and 0.5 parts of rice bran wax are added into a high-speed mixer and dispersed evenly; the mixture is transported to a storage bin for standby use.
[0049] (2) The mixed material is weighed by a loss-in-weight scale and added to a co-rotating twin-screw extruder for melt extrusion and granulation, wherein the co-rotating twin-screw extruder uses a screw length-diameter ratio of 35:1; the extrusion temperature of each zone is controlled as follows: zone 1 220°C; zone 2 280°C; zone 3 310°C; zone 4 290°C; zone 5 260°C; zone 6 240°C; zone 7 290°C; zone 8 300°C; zone 9 300°C; zone 10 320°C; alkali-free continuous glass fiber is added to the side feed port of zone 5 , by controlling the screw speed and the number of glass fiber added, ensuring that the amount of glass fiber added is 40 parts; adding 5 parts of hollow glass microbeads (brand iM16K) through a loss-in-weight scale at the side feeding port of zone seven; pumping 0.3 parts of silane coupling agent (brand KH-560) into the side feeding port of zone eight through a metering pump; through screw shearing dispersion, melt extrusion, water-cooled strand pelletizing, screening, drying and packaging, a damping and noise-reducing polyphenylene sulfide composite material is obtained.
[0050] Comparative Example 1:
[0051] According to the weight of the formula, 40 parts of polyphenylene sulfide, 0.5 parts of rice bran wax and 1.0 parts of black masterbatch are added into a high-speed mixer and dispersed evenly; the mixture is transported to a storage bin for standby use;
[0052] S2: The mixed material is weighed by a loss-in-weight scale and added to a co-rotating twin-screw extruder for melt extrusion and granulation. The co-rotating twin-screw extruder uses a screw length-diameter ratio of 35:1. The extrusion temperature of each zone is: 220℃ for zone 1; 280℃ for zone 2; 310℃ for zone 3; 290℃ for zone 4; 260℃ for zone 5; 240℃ for zone 6; 290℃ for zone 7; 300℃ for zone 8; 300℃ for zone 9; 320℃ for zone 10. Alkali-free continuous glass fiber is added to the side feed port of zone 5. , by controlling the screw speed and the number of glass fiber added, ensuring that the amount of glass fiber added is 45 parts; adding 5 parts of hollow glass microbeads (brand iM16K) through a loss-in-weight scale at the side feeding port of zone seven; pumping 0.3 parts of silane coupling agent (brand KH-560) into the side feeding port of zone eight through a metering pump; through screw shearing dispersion, melt extrusion, water-cooled strand pelletizing, screening, drying and packaging, a damping and noise reduction polyphenylene sulfide composite material is obtained.
[0053] Comparative Example 2:
[0054] According to the weight of the formula, 40 parts of polyphenylene sulfide, 5 parts of interpenetrating network polymer obtained by blending SBS and LLDPE and cross-linking initiated by benzoyl peroxide, 0.5 parts of rice bran wax, 1.0 parts of black masterbatch, 5 parts of hollow glass microspheres (brand iM16K), and 0.3 parts of silane coupling agent (brand KH-560) are added into a high-speed mixer and dispersed evenly; the mixture is transported to a storage bin for standby use.
[0055] The mixed material is weighed by a loss-in-weight scale and added into a co-rotating twin-screw extruder for melt extrusion and granulation, wherein the co-rotating twin-screw extruder uses a screw length-to-diameter ratio of 35:1; the extrusion temperature control of each zone is: 220°C for zone one; 280°C for zone two; 310°C for zone three; 290°C for zone four; 260°C for zone five; 240°C for zone six; 290°C for zone seven; 300°C for zone eight; 300°C for zone nine; and 320°C for zone ten; alkali-free continuous glass fiber is added to the side feeding port of zone five, and the amount of glass fiber added is ensured to be 45 parts by controlling the screw speed and the number of glass fiber added strands; a damping and noise-reducing polyphenylene sulfide composite material is obtained by screw shearing dispersion, melt extrusion, water-cooled strand cutting, screening, drying and packaging.
[0056] Comparative Example 3:
[0057] According to the formula weight, 40 parts of polyphenylene sulfide, 0.5 parts of rice bran wax, 5 parts of elastomer ethylene-vinyl acetate copolymer (EVA), and 1.0 parts of black masterbatch are added into a high-speed mixer and dispersed evenly; the mixture is transported to a storage bin for standby use.
[0058] The mixed material is weighed by a loss-in-weight scale and added to a co-rotating twin-screw extruder for melt extrusion and granulation. The co-rotating twin-screw extruder uses a screw length-diameter ratio of 35:1. The extrusion temperature of each zone is: 220°C for zone 1; 280°C for zone 2; 310°C for zone 3; 290°C for zone 4; 260°C for zone 5; 240°C for zone 6; 290°C for zone 7; 300°C for zone 8; 300°C for zone 9; and 320°C for zone 10. Alkali-free continuous glass fiber is added to the side feed port of zone 5. The screw speed and the number of glass fiber added were controlled to ensure that the amount of glass fiber added was 45 parts; 5 parts of hollow glass microbeads (brand iM16K) were added through a loss-in-weight scale at the side feeding port of zone seven; 0.3 parts of silane coupling agent (brand KH-560) were pumped into the side feeding port of zone eight through a metering pump; a damping and noise-reducing polyphenylene sulfide composite material was obtained through screw shearing dispersion, melt extrusion, water-cooled strand pelletizing, screening, drying and packaging.
[0059] Further, the samples obtained from Examples 1-3 and Comparative Examples 1-3 were used for injection molding of cylinder head covers and for cylinder heads of engines, as shown in the attached Figure 1 , select 4 points to test the noise level at a distance of 20cm in the near field to measure the damping noise reduction performance. The test data is shown in Table 1:
[0060] Table 1 Performance test results
[0061]
[0062] By selecting 4 points to test the noise level at a distance of 20 cm in the near field, the overall noise of Examples 1-3 is relatively low. Since Comparative Example 1 does not use shape memory material, its noise reduction effect is significantly reduced; even if Comparative Example 3 uses the painful elastomer ethylene-vinyl acetate copolymer (EVA), its noise reduction effect is also limited; Since the hollow glass microspheres are directly added in Comparative Example 1, they are easily sheared and damaged during the screw extruder processing, and it is difficult to achieve the expected noise reduction purpose.
[0063] Obviously, the technical solution of the present invention uses shape memory polymers in a glass fiber reinforced polyphenylene sulfide system. When the molecular chain segments are subjected to external vibration energy, they change their conformation through internal rotation in the main chain, and at the same time, they move, slip, and disentangle to generate internal friction, thereby instantly converting the external vibration energy into heat energy dissipation, thereby achieving damping and noise reduction; during extrusion granulation, hollow glass microbeads are added after the glass fiber is sheared, and a coupling agent is added at the end, so that the hollow glass microbeads are mixed under low viscosity conditions, ensuring that the hollow glass microbeads are not easily sheared and damaged during screw extruder processing, further synergistically improving the damping and noise reduction effect.
[0064] In the description of the present invention, it is necessary to understand that the terms "upper", "lower", "bottom", "one end", "top", "middle", "the other end", "coaxial", "one side", "inside", "front", "center", "both ends", etc., indicating the orientation or position relationship are based on the orientation or position relationship shown in the drawings, which are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0065] In the present invention, unless otherwise clearly stipulated and limited, the terms such as "setting", "installation", "connection", "fixation", "hinge" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral one; it can be a mechanical connection or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium; it can be the internal connection of two elements or the interaction relationship between two elements. Unless otherwise clearly defined, for ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to the specific circumstances.
[0066] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.
Claims
1. A damping and noise reduction polyphenylene sulfide composite material, characterized in that: The invention comprises specific weight portions of polyphenylene sulfide 40-55 parts, glass fiber 35-45 parts, shape memory polymer 3-5 parts, hollow glass microspheres 3-5 parts, lubricant 0.3-0.5 parts, coupling agent 0.2-0.5 parts and masterbatch 0-2 parts.
2. The damping and noise reduction polyphenylene sulfide composite material according to claim 1, characterized in that: The shape memory polymer is preferably based on polyurethane and / or styrene-butadiene-styrene triblock copolymer.
3. The damping and noise reduction polyphenylene sulfide composite material according to claim 1, characterized in that: The shape memory polymer is selected from a cross-linked polymer of polyurethane and epoxy resin, and / or a cross-linked polymer of styrene-butadiene-styrene triblock copolymer and linear low-density polyethylene.
4. The damping and noise reduction polyphenylene sulfide composite material according to claim 1, characterized in that: The hollow glass microspheres have a particle size of 20 μm and a compressive strength of ≥110 MPa.
5. The damping and noise reduction polyphenylene sulfide composite material according to claim 1, characterized in that: The glass fiber is selected from alkali-free continuous glass fiber.
6. The damping and noise reduction polyphenylene sulfide composite material according to claim 1, characterized in that: The lubricant is selected from one or more of silicone powder, silicone masterbatch, and rice bran wax.
7. The damping and noise reduction polyphenylene sulfide composite material according to claim 1, characterized in that: The coupling agent is a silane coupling agent.
8. The method for preparing the damping and noise reduction polyphenylene sulfide composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: 40-55 parts of the polyphenylene sulfide, 3-5 parts of the shape memory polymer, 0.3-0.5 parts of the lubricant, and 0-2 parts of the masterbatch are mixed at a high speed and uniformly dispersed to obtain a mixture; S2: adding the mixed material into a co-rotating twin-screw extruder for melt extrusion granulation, adding 35-45 parts of alkali-free continuous glass fiber, 3-5 parts of hollow glass microbeads and 0.2-0.5 parts of coupling agent during the melt extrusion granulation process, screening and drying after granulation to obtain the damping and noise reduction polyphenylene sulfide composite material.
9. The preparation method according to claim 8, characterized in that: The length-to-diameter ratio of the screw of the co-rotating twin-screw extruder is 35:1, and it includes ten extrusion temperature control zones in sequence, and the extrusion temperature control of each zone is: zone one 220-260°C; zone two 280-300°C; zone three 310-320°C; zone four 280-290°C; zone five 220-260°C; zone six 240-260°C; zone seven 290-300°C; zone eight 290-300°C; zone nine 290-300°C and zone ten 300-320°C.
10. The preparation method according to claim 9, characterized in that: The alkali-free continuous glass fiber is added from the feeding port on the side of the fifth zone; the hollow glass microspheres are added from the feeding port on the side of the seventh zone; and the coupling agent is added from the feeding port on the side of the eighth zone.
Citation Information
Patent Citations
Lightweight noise-reduction polyphenylene sulfide (PPS) material and its preparation method
CN103173014A